2008
DOI: 10.47102/annals-acadmedsg.v37n6p477
|View full text |Cite
|
Sign up to set email alerts
|

A Global Perspective on Avian Influenza

Abstract: Global public health security is both a collective aspiration and a mutual responsibility that demands cooperative action at all levels. The expansion of the current H5N1 avian influenza enzootic and its incursion into human health presents a real and significant threat of an influenza pandemic. The world has for the first time an unprecedented opportunity for pandemic preparation. Current global efforts to tackle the H5N1 pandemic threat are centred around the framework of the International Health Regulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This is consistent with the greater efficacy of pONB US, pONB NS, and dONB NS + US compared to dONB US observed in our analysis. Thus, local blockade using a peripheral nerve stimulator remains the key to improving the efficacy of ONB, 38 since it enhances the safety of the block by improving accuracy and reducing the dose of the local anesthetic. We also found that pONB US and dONB NS had superior effects compared to tONB.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the greater efficacy of pONB US, pONB NS, and dONB NS + US compared to dONB US observed in our analysis. Thus, local blockade using a peripheral nerve stimulator remains the key to improving the efficacy of ONB, 38 since it enhances the safety of the block by improving accuracy and reducing the dose of the local anesthetic. We also found that pONB US and dONB NS had superior effects compared to tONB.…”
Section: Discussionmentioning
confidence: 99%
“…Regional anesthesia has many advantages such as lack of airway instrumentation, avoidance of polypharmacy, especially opioids, early recognition of bladder perforation, and fewer incidences of nausea and vomiting. The disadvantage of spinal anesthesia is the inability to prevent adductor spasms due to the obturator reflex [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The obturator reflex occurs when the obturator nerve is directly stimulated by the electrical current transmitted by the resectoscope, especially when the tumor is located on the lateral and posterolateral wall of the bladder, resulting in adductor spasm. This spasm is undesirable as it may result in disastrous consequences such as bladder perforation, excessive bleeding, and incomplete resection of tumors [ 1 , 2 ]. The frequency of severe adductor muscle jerks in patients undergoing TURBT for laterally located bladder tumors or large intraurethral prostatic adenomas is about 20-40% [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…17 The world is quite far from achieving the noble goals of the Alma-Ata declaration of 1978 by WHO, which recognised health as a fundamental human right of all countries and not just of the wealthy ones. 18 Moving beyond the global perspective of avian influenza by the WHO leadership 19 are complementary articles from Singapore 20,21 and Hong Kong 22 about preparations for pandemic influenza. The SARS crisis affected both cities drastically, and many valuable lessons have been learnt from that episode.…”
mentioning
confidence: 99%